Guías móviles en Realidad Virtual para la interpretación del patrimonio. Un caso práctico: Ruta del Megalitismo de Gorafe - Jon Arambarri Basáñez (Virtual Archaeology Review, 2012)
Although early prehistoric findings belong to Middle Paleolithic (30,000 to 50,000 years ago), it was 6,000 years ago when Gorafe Valley was occupied by tribes characterized by collective burials in tombs made of big blocks, that is, in dolmens (Megalithic culture of Middle Neolithic). Nowadays, Gorafe holds the biggest proportion of dolmens in Europe: 198 spread in the 10 necropolis that surround the village. The city council of Gorafe expresses the need to know and interpret these dolmens through a mobile device which does not require Internet connection. This way, visitors will be able to enjoy and interpret their Megalithic tour when they visit Sierra Nevada.